A wide-band radar wave stealth composite material and preparation method thereof
By adopting a four-layer structure wide-band radar wave stealth composite material, the problem of existing stealth coatings falling off under high shear, high temperature and high humidity conditions is solved, and the effective absorption of wide-band radar waves and the improvement of aircraft stealth performance is achieved.
Patent Information
- Application Number
- CN202411977586.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing stealth coatings are prone to fall off under high shear, high temperature and high humidity service conditions, resulting in a greatly reduced stealth performance of the aircraft and cannot meet the requirements of modern aircraft for wide-band radar wave stealth.
A wide-band radar wave stealth composite material with a four-layer structure, including a high-band, medium-band and low-band radar wave absorption layer, and a radar wave reflective layer, is formed by applying different proportions of epoxy resin and wave absorbing components on carbon fiber cloth and quartz cloth to form a composite material with wide-band wave absorbing ability.
It realizes two effective absorption of wide-band radar waves, improves the stealth performance of the aircraft, and has excellent mechanical properties, which can be integrated with the aircraft components to replace the traditional stealth coating.
Smart Images

Figure CN119779093A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional materials, and particularly relates to a broadband radar wave stealth composite material and a preparation method thereof. Background Art
[0002] Radar wave stealth is a method in which stealth materials on the surface of an aircraft convert electromagnetic waves emitted by the radar into heat or other forms of energy and release them, thereby achieving the purpose of aircraft stealth.
[0003] The operating frequency range of most aviation or maritime radars is from L band to Ku band, and the corresponding frequency is in the range of 1 to 18 GHz. Conventional stealth coatings generally have good stealth performance in the 4 to 8 GHz or 8 to 12 GHz frequency bands. Conventional stealth coatings can no longer meet the requirements of modern aircraft for wide-band radar wave stealth.
[0004] The stealth of an aircraft to radar is achieved by coating the outer surface of the aircraft's structural parts with a stealth coating. The stealth coating material is bonded to the outer surface of the aircraft by adhesive force. The stealth coating is easy to fall off under service conditions of high shear force, high temperature, and high humidity, which greatly reduces the stealth performance of the aircraft.
[0005] Therefore, it is necessary to develop a stealth material that can not only meet the requirements of wide-band radar wave stealth, but also be integrated with aircraft components. Summary of the invention
[0006] The purpose of the present invention is to overcome the defects in the prior art and provide a wide-band radar wave stealth composite material and a preparation method thereof.
[0007] The present invention provides a wide-band radar wave stealth composite material, comprising a high-band radar wave absorbing layer, a medium-band radar wave absorbing layer, a low-band radar wave absorbing layer and a radar wave reflecting layer which are sequentially cured from top to bottom;
[0008] The high-frequency radar wave absorbing layer is used to absorb radar waves with a frequency between 12.5 and 18 GHz;
[0009] The mid-frequency radar wave absorbing layer is used to absorb radar waves with a frequency between 4 and 12.5 GHz;
[0010] The low-frequency radar wave absorbing layer is used to absorb radar waves with a frequency between 1 and 4 GHz;
[0011] The high-frequency radar wave absorbing layer comprises a coating material I coated on a carbon fiber cloth and a coating material II coated on a quartz cloth, wherein the coating material I is a mixture of 50 to 60 parts of epoxy resin A and 10 to 15 parts of curing agent B; the coating material II is a wave absorbing component C added to the coating material I at 1 to 6% of the weight of the coating material I;
[0012] The intermediate frequency radar wave absorbing layer comprises a coating material I coated on a carbon fiber cloth and a coating material III coated on a quartz cloth, wherein the coating material III is a wave absorbing component D added to the coating material I at 35-50% of the weight of the coating material I;
[0013] The low-frequency radar wave absorbing layer includes a coating material I coated on a carbon fiber cloth and a coating material IV coated on a quartz cloth, wherein the coating material IV is a wave absorbing component E added to the coating material I at 35-50% of the weight of the coating material I;
[0014] The radar wave reflection layer is a carbon fiber reinforced epoxy resin-based composite material with a thickness of 0.5 to 1.2 mm.
[0015] In a further embodiment, the epoxy resin A is resorcinol diglycidyl ether or bisphenol F diglycidyl ether, and the viscosity of the epoxy resin A is 300 mPa·s to 900 mPa·s.
[0016] In a further embodiment, the curing agent B is dicyandiamide or diaminodiphenyl sulfone.
[0017] A further solution is that the radar absorbing component C is a mixture of Fe(CO)5 powder and carbon black powder in a ratio of 1:1.
[0018] A further solution is that the radar absorbing component D is BaFe 12 O 19 Powder and CaFe 12 O 19 The powder is mixed in a 1:1 ratio.
[0019] A further solution is that the radar absorbing component E is a mixture of FeSiAl powder and FeSiCr powder in a ratio of 1:1.
[0020] A further solution is that the quartz cloth has a thickness of 0.1 to 0.4 mm and a surface density of 80 to 500 g / m 2 The carbon fiber cloth has a thickness of 0.05 to 0.4 mm and a surface density of 50 to 400 g / m 2 .
[0021] A second aspect of the present invention provides a method for preparing a radar broadband stealth composite material, which is used to prepare the above-mentioned radar broadband stealth composite material, comprising the following steps:
[0022] S1. Weigh the coating material I and the absorbing component C, absorbing component D, and absorbing component E in proportion;
[0023] S2, respectively dispersing the coating material I and the absorbing component C, the coating material I and the absorbing component D, and the coating material I and the absorbing component E using a high-speed disperser to obtain coating material II, coating material III, and coating material IV, respectively;
[0024] S3, brushing the coating material I onto the carbon fiber cloth to form a prepreg I, laying the prepreg I, brushing the coating material II onto the quartz cloth to obtain a prepreg A, and laying the prepreg A;
[0025] S4, brushing the coating material I onto the carbon fiber cloth to obtain the prepreg II, laying the prepreg II, brushing the coating material III onto the quartz cloth to obtain the prepreg B, and laying the prepreg B;
[0026] S5, brushing the coating material I onto the carbon fiber cloth to obtain the prepreg III, laying the prepreg III, brushing the coating material III onto the quartz cloth to obtain the prepreg C, and laying the prepreg C;
[0027] S6, curing and molding the prepreg I ply and the prepreg A ply to obtain a high-frequency radar wave absorbing layer, curing and molding the prepreg II ply and the prepreg B ply to obtain a medium-frequency radar wave absorbing layer, and curing and molding the prepreg III ply and the prepreg C ply to obtain a low-frequency radar wave absorbing layer;
[0028] A further solution is that the dispersion time in step S2 is 5 to 8 minutes; the curing temperature in step S6 is 120-140° C., the curing pressure is 0.6 to 1.2 MPa, and the curing time is 2 to 3 hours.
[0029] A further solution is that in step S3, the coating material I is 120 g / m 2 Apply to the carbon fiber cloth to form prepreg I, the prepreg I layer thickness is 0.5-1.2mm; coating material II is 120g / m 2 Brushing onto quartz cloth to obtain prepreg A, wherein the prepreg A has a layer thickness of 1.6 to 2.0 mm;
[0030] In step S4, the coating material I is 120 g / m 2 The prepreg II is coated on the carbon fiber cloth to obtain a prepreg II, wherein the prepreg II has a layer thickness of 1.4 to 1.8 mm; the coating material III is 120 g / m 2 Brushing onto quartz cloth to obtain prepreg B, wherein the prepreg B has a layer thickness of 0.4 to 0.8 mm;
[0031] In step S5, the coating material I is 120 g / m 2 The prepreg III is applied to the carbon fiber cloth to obtain a prepreg III, wherein the prepreg III has a ply thickness of 1.4 to 1.8 mm; the coating material III is 120 g / m 2 The prepreg C is obtained by brushing it onto a quartz cloth. The prepreg C has a layer thickness of 0.4 to 0.8 mm.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] The aircraft radar stealth material of the present invention adopts a four-layer structure, which includes a high-frequency radar wave absorption layer, a medium-frequency radar wave absorption layer, a low-frequency radar wave absorption layer and a radar wave reflection layer from top to bottom; broadband radar waves are absorbed after passing through different absorption layers, and the remaining radar waves are reflected by the reflection layer and then enter the absorption layer again, thereby achieving secondary effective absorption of broadband radar waves.
[0034] The present invention is to evenly disperse the absorbing material in the resin and form a fiber-reinforced composite material with stealth performance together with the reinforcing fiber. In addition to having excellent stealth performance, the fiber-reinforced composite material also has excellent mechanical properties and can be integrated into the stealth structure of the aircraft, replacing the stealth coating to achieve structural and functional integration.
[0035] The present invention uses epoxy resin and curing agent as carriers, uniformly disperses a variety of absorbing materials in the resin carrier to form a resin matrix with broadband absorbing ability, and then compounds the resin with a reinforcement through a hot melt process to form a stealth prepreg. The stealth prepreg can be implemented through a variety of processes such as lamination and winding, thereby broadening the molding process of stealth materials.
[0036] The preparation process of the present invention is simple and the molding is convenient. The stealth prepreg can be prepared by compounding a resin film with a fiber cloth by manual brushing or hot melt film process. The prepreg can be used for winding, molding, autoclave and other molding processes to achieve diversified molding process methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The following drawings are only used to illustrate and explain the present invention, and are not used to limit the scope of the present invention, wherein:
[0038] Figure 1 : A schematic diagram of the cross-sectional structure of the broadband radar wave stealth composite material of the present invention;
[0039] Figure 2 :Attenuation results of Example 1 under 1~18GHz radar waves;
[0040] Figure 3 :Attenuation results of Example 2 under 1~18GHz radar waves;
[0041] Figure 4 :Attenuation results of Example 3 under 1~18GHz radar waves;
[0042] In the figure: 1. Low-frequency radar wave absorption layer; 2. Mid-frequency radar wave absorption layer; 3. High-frequency radar wave absorption layer; 4. Radar wave reflection layer. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solution, design method and advantages of the present invention clearer, the present invention is further described in detail by specific embodiments in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0044] Example 1
[0045] The present invention provides a broadband radar wave stealth composite material, the cross-sectional structure of which is as follows: Figure 1 As shown, from top to bottom are the high-frequency radar wave absorption layer 3, the medium-frequency radar wave absorption layer 2, the low-frequency radar wave absorption layer 1 and the radar wave reflection layer 4, wherein the absorption layer is made of quartz fiber reinforced epoxy resin-based composite material, and the reflection layer is made of carbon fiber reinforced epoxy resin-based composite material. The thickness of the high-frequency radar wave absorption layer is 1.8mm; the thickness of the medium-frequency radar wave absorption layer is 1.6mm; the thickness of the low-frequency radar wave absorption layer is 0.6mm; the thickness of the reflection layer is 0.8mm, and the total thickness is 4.8mm. The high-frequency radar wave absorption layer is used to absorb radar waves with frequencies between 12.5 and 18GHz; the medium-frequency radar wave absorption layer is used to absorb radar waves with frequencies between 4 and 12.5GHz; the low-frequency radar wave absorption layer is used to absorb radar waves with frequencies between 1 and 4GHz;
[0046] The high-frequency radar wave absorbing layer comprises a coating material I coated on a carbon fiber cloth and a coating material II coated on a quartz cloth, wherein the coating material I is a mixture of 50-60 parts of epoxy resin A and 10-15 parts of curing agent B; the coating material II is a wave absorbing component C added to the coating material I at 1-6% of the weight of the coating material I; the medium-frequency radar wave absorbing layer comprises a coating material I coated on a carbon fiber cloth and a coating material III coated on a quartz cloth, wherein the coating material III is a wave absorbing component D added to the coating material I at 35-50% of the weight of the coating material I; the low-frequency radar wave absorbing layer comprises a coating material I coated on a carbon fiber cloth and a coating material IV coated on a quartz cloth, wherein the coating material IV is a wave absorbing component E added to the coating material I at 35-50% of the weight of the coating material I; the radar wave reflecting layer is a carbon fiber reinforced epoxy resin-based composite material with a thickness of 0.5-1.2 mm.
[0047] In the above, the epoxy resin A is resorcinol diglycidyl ether or bisphenol F diglycidyl ether, the epoxy resin A has a viscosity of 300mPa·s to 900mPa·s, the curing agent B is dicyandiamide or diaminodiphenyl sulfone, the radar absorbing component C is a mixture of Fe(CO)5 powder and carbon black powder in a ratio of 1:1, and the radar absorbing component D is BaFe 12 O 19 Powder and CaFe 12 O 19 The powder is mixed in a ratio of 1:1, the radar absorbing component E is a mixture of FeSiAl powder and FeSiCr powder in a ratio of 1:1, the quartz cloth has a thickness of 0.1-0.4 mm and a surface density of 80-500 g / m 2 The carbon fiber cloth has a thickness of 0.05 to 0.4 mm and a surface density of 50 to 400 g / m 2 .
[0048] The preparation of the above-mentioned wide-band radar wave stealth composite material includes the following steps:
[0049] S1: By weight, 50 parts of resorcinol diglycidyl ether and 10 parts of diaminodiphenyl sulfone were stirred in a stirring tank at a stirring speed of 6 r / min and a stirring temperature of 25° C. for 8 minutes to obtain a mixed component X, and X was taken out from the stirring tank for use;
[0050] S2: Based on the weight of X, 1% Fe(CO)5 powder and 1% carbon black powder were added to the mixed component X in a ratio of 1:1, and stirred for 5 minutes at a stirring speed of 700 r / min and a stirring temperature of 25°C to obtain a mixed component F;
[0051] S3: Based on the weight of X, BaFe with a mass fraction of 35% 12 O 19 , and 35% CaFe 12 O 19 The powder was added to the mixed component X at a ratio of 1:1, and stirred for 5 minutes at a stirring speed of 700 r / min and a stirring temperature of 25°C to obtain a mixed component G;
[0052] S4: Based on the weight of X, 35% FeSiAl powder and 35% FeSiCr powder were added to the mixed component X in a ratio of 1:1, and stirred for 5 minutes at a stirring speed of 700 r / min and a stirring temperature of 25° C. to obtain a mixed component H;
[0053] S5: Brush 120g of mixed component X to 1.0m 2Prepreg X is made on the carbon fiber cloth, and 4 layers of rectangular prepreg are laid out for use;
[0054] S6: Brush 120g of mixed component F to 1.0m 2 Prepreg F is made on the quartz cloth, and 9 layers of rectangular prepreg are laid out for use;
[0055] S7: Brush 120g of mixed component G to 1.0m 2 Prepreg G is made on the quartz cloth, and 8 layers of rectangular prepreg are laid out for use;
[0056] S8: Brush 60g of mixed component H to 0.5m 2 Prepreg H is made on the quartz cloth, and three layers of rectangular prepreg are laid out for use;
[0057] S9: stacking the prepregs prepared in S5 to S8 in a top-down order;
[0058] S10: placing the laminate obtained in S9 on a hot press, heating the temperature to 90°C at a heating rate of 0.5°C / min, keeping it at 90°C for 1 hour, adjusting the pressure to 0.8MPa, heating from 90° to 180°C at a rate of 0.5°C / min, keeping it at 180°C for 2 hours, and then cooling it down to below 60°C with the furnace to obtain the radar broadband stealth composite material of the present invention.
[0059] The arch method is used to test the reflection loss of composite materials in the 1-18 GHz frequency band. The unit of reflection loss is dB. Each test result is for 5 samples, and the test result is the average value of 5 samples. The test results are shown in Figure 2 .
[0060] Example 2
[0061] The process of preparing the broadband radar wave stealth composite material in this embodiment is as follows:
[0062] S1: By weight, 55 parts of bisphenol F diglycidyl ether and 13 parts of dicyandiamide were stirred in a stirring tank at a stirring speed of 8 r / min and a stirring temperature of 25° C. for 10 min to obtain a mixed component X, and X was taken out from the stirring tank for later use;
[0063] S2: Based on the weight of X, 3.0% Fe(CO)5 powder and 3.0% carbon black powder were added to the mixed component X in a ratio of 1:1, and stirred for 5 minutes at a stirring speed of 700 r / min and a stirring temperature of 25°C to obtain a mixed component F;
[0064] S3: Based on the weight of X, BaFe with a mass fraction of 40% 12 O 19 Powder and 40% CaFe12 O 19 The powder was added to the mixed component X at a ratio of 1:1, and stirred for 5 minutes at a stirring speed of 700 r / min and a stirring temperature of 25°C to obtain a mixed component G;
[0065] S4: Based on the weight of X, 42% FeSiAl powder and 42% FeSiCr powder were added to the mixed component X in a ratio of 1:1, and stirred for 5 minutes at a stirring speed of 700 r / min and a stirring temperature of 25° C. to obtain a mixed component H;
[0066] S5: Brush 120g of mixed component X to 1.0m 2 Prepreg X is made on the carbon fiber cloth, and 4 layers of rectangular prepreg are laid out for use;
[0067] S6: Brush 120g of mixed component F to 1.0m 2 Prepreg F is made on the quartz cloth, and 9 layers of rectangular prepreg are laid out for use;
[0068] S7: Brush 120g of mixed component G to 1.0m 2 Prepreg G is made on the quartz cloth, and 8 layers of rectangular prepreg are stacked and set aside;
[0069] S8: Brush 60g of mixed component H to 0.5m 2 Prepreg H is made on the quartz cloth, and three layers of rectangular prepreg are stacked and set aside;
[0070] S9: stacking the prepregs prepared in S5 to S8 in a top-down order;
[0071] S10: placing the laminate obtained in S9 on a hot press, heating the temperature to 90°C at a heating rate of 0.5°C / min, keeping it at 90°C for 1 hour, adjusting the pressure to 0.8MPa, heating from 90° to 180°C at a rate of 0.5°C / min, keeping it at 180°C for 2 hours, and then cooling it down to below 60°C with the furnace to obtain the radar broadband stealth composite material of the present invention.
[0072] The arch method is used to test the reflection loss of composite materials in the 1-18 GHz frequency band. The unit of reflection loss is dB. Each test result is for 5 samples, and the test result is the average value of 5 samples. The test results are shown in Figure 3 .
[0073] Example 3
[0074] The process of preparing the broadband radar wave stealth composite material in this embodiment is as follows:
[0075] S1: By weight, 60 parts of resorcinol diglycidyl ether and 15 parts of dicyandiamide are stirred in a stirring tank at a stirring speed of 10 r / min and a stirring temperature of 30° C. for 15 minutes to obtain a mixed component X, and X is taken out from the stirring tank for standby use;
[0076] S2: Based on the weight of X, 6.0% Fe(CO)5 powder and 6.0% carbon black powder were added to the mixed component X in a ratio of 1:1, and stirred for 5 minutes at a stirring speed of 700 r / min and a stirring temperature of 25°C to obtain a mixed component F;
[0077] S3: Based on the weight of X, BaFe with a mass fraction of 50% 12 O 19 Powder and 50% CaFe 12 O 19 The powder was added to the mixed component X at a ratio of 1:1, and stirred for 5 minutes at a stirring speed of 700 r / min and a stirring temperature of 25°C to obtain a mixed component G;
[0078] S4: Based on the weight of X, 50% FeSiAl powder and 50% FeSiCr powder are added to the mixed component X in a ratio of 1:1, and stirred for 5 minutes at a stirring speed of 700 r / min and a stirring temperature of 25° C. to obtain a mixed component H;
[0079] S5: Brush 120g of mixed component X to 1.0m 2 Prepreg X is made on the carbon fiber cloth, and 4 layers of rectangular prepreg are stacked and set aside;
[0080] S6: Brush 120g of mixed component F to 1.0m 2 Prepreg F is made on the quartz cloth, and 9 layers of rectangular prepreg are stacked and set aside;
[0081] S7: Brush 120g of mixed component G to 1.0m 2 Prepreg G is made on the quartz cloth, and 8 layers of rectangular prepreg are stacked and set aside;
[0082] S8: Brush 120g of mixed component H to 1.0m 2 Prepreg H is made on the quartz cloth, and three layers of rectangular prepreg are stacked and set aside;
[0083] S9: stacking the prepregs prepared in S5 to S7 in a top-down order;
[0084] S10: placing the laminate obtained in S9 on a hot press, heating the temperature to 90°C at a heating rate of 0.5°C / min, keeping it at 90°C for 1 hour, adjusting the pressure to 0.8MPa, heating from 90° to 180°C at a rate of 0.5°C / min, keeping it at 180°C for 2 hours, and then cooling it down to below 60°C with the furnace to obtain the radar broadband stealth composite material of the present invention.
[0085] The arch method is used to test the reflection loss of composite materials in the 1-18 GHz frequency band. The unit of reflection loss is dB. Each test result is for 5 samples, and the test result is the average value of 5 samples. The test results are shown in Figure 4 .
[0086] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A broadband radar wave stealth composite material, characterized in that: It includes a high-frequency radar wave absorbing layer, a medium-frequency radar wave absorbing layer, a low-frequency radar wave absorbing layer and a radar wave reflecting layer which are solidified and formed in sequence from top to bottom; The high-frequency radar wave absorbing layer is used to absorb radar waves with a frequency between 12.5 and 18 GHz; The mid-frequency radar wave absorbing layer is used to absorb radar waves with a frequency between 4 and 12.5 GHz; The low-frequency radar wave absorbing layer is used to absorb radar waves with a frequency between 1 and 4 GHz; The high-frequency radar wave absorbing layer comprises a coating material I coated on a carbon fiber cloth and a coating material II coated on a quartz cloth, wherein the coating material I is a mixture of 50 to 60 parts of epoxy resin A and 10 to 15 parts of curing agent B; the coating material II is a wave absorbing component C added to the coating material I at 1 to 6% of the weight of the coating material I; The intermediate frequency radar wave absorbing layer comprises a coating material I coated on a carbon fiber cloth and a coating material III coated on a quartz cloth, wherein the coating material III is a wave absorbing component D added to the coating material I at 35-50% of the weight of the coating material I; The low-frequency radar wave absorbing layer includes a coating material I coated on a carbon fiber cloth and a coating material IV coated on a quartz cloth, wherein the coating material IV is a wave absorbing component E added to the coating material I at 35-50% of the weight of the coating material I; The radar wave reflection layer is a carbon fiber reinforced epoxy resin-based composite material with a thickness of 0.5 to 1.2 mm.
2. A broadband radar wave stealth composite material according to claim 1, characterized in that: The epoxy resin A is resorcinol diglycidyl ether or bisphenol F diglycidyl ether, and the viscosity of the epoxy resin A is 300 mPa·s to 900 mPa·s.
3. A wide-band radar wave stealth composite material according to claim 1, characterized in that: The curing agent B is dicyandiamide or diaminodiphenyl sulfone.
4. A broadband radar wave stealth composite material according to claim 1, characterized in that: The radar absorbing component C is a mixture of Fe(CO)5 powder and carbon black powder in a ratio of 1:
1.
5. A broadband radar wave stealth composite material according to claim 1, characterized in that: The radar absorbing component D is BaFe 12 O 19 Powder and CaFe 12 O 19 The powder is mixed in a 1:1 ratio.
6. A broadband radar wave stealth composite material according to claim 1, characterized in that: The radar absorbing component E is a mixture of FeSiAl powder and FeSiCr powder in a ratio of 1:
1.
7. A broadband radar wave stealth composite material according to claim 1, characterized in that: The thickness of the quartz cloth is 0.1-0.4 mm, and the surface density is 80-500 g / m 2 The carbon fiber cloth has a thickness of 0.05 to 0.4 mm and a surface density of 50 to 400 g / m 2 .
8. A method for preparing a broadband radar wave stealth composite material, used for preparing the broadband radar stealth composite material according to any one of claims 1 to 7, characterized in that: The steps include: S1. Weigh the coating material I and the absorbing component C, absorbing component D, and absorbing component E in proportion; S2, respectively dispersing the coating material I and the absorbing component C, the coating material I and the absorbing component D, and the coating material I and the absorbing component E using a high-speed disperser to obtain coating material II, coating material III, and coating material IV, respectively; S3, brushing the coating material I onto the carbon fiber cloth to form a prepreg I, laying the prepreg I, brushing the coating material II onto the quartz cloth to obtain a prepreg A, and laying the prepreg A; S4, brushing the coating material I onto the carbon fiber cloth to obtain the prepreg II, laying the prepreg II, brushing the coating material III onto the quartz cloth to obtain the prepreg B, and laying the prepreg B; S5, brushing the coating material I onto the carbon fiber cloth to obtain the prepreg III, laying the prepreg III, brushing the coating material III onto the quartz cloth to obtain the prepreg C, and laying the prepreg C; S6. The prepreg I plies and the prepreg A plies are cured to obtain a high-frequency radar wave absorbing layer, the prepreg II plies and the prepreg B plies are cured to obtain a medium-frequency radar wave absorbing layer, and the prepreg III plies and the prepreg C plies are cured to obtain a low-frequency radar wave absorbing layer.
9. A radar broadband stealth composite material according to claim 8, characterized in that: The dispersion time in step S2 is 5 to 8 minutes; the curing temperature in step S6 is 120-140° C., the curing pressure is 0.6 to 1.2 MPa, and the curing time is 2 to 3 hours.
10. A radar broadband stealth composite material according to claim 9, characterized in that: In step S3, the coating material I is 120g / m 2 Apply to the carbon fiber cloth to form prepreg I, the prepreg I layer thickness is 0.5-1.2mm; coating material II is 120g / m 2 Brushing onto quartz cloth to obtain prepreg A, wherein the prepreg A has a layer thickness of 1.6 to 2.0 mm; In step S4, the coating material I is 120 g / m 2 The prepreg II is coated on the carbon fiber cloth to obtain a prepreg II, wherein the prepreg II has a layer thickness of 1.4 to 1.8 mm; the coating material III is 120 g / m 2 Brushing onto quartz cloth to obtain prepreg B, wherein the prepreg B has a layer thickness of 0.4 to 0.8 mm; In step S5, the coating material I is 120 g / m 2 The prepreg III is applied to the carbon fiber cloth to obtain a prepreg III, wherein the prepreg III has a ply thickness of 1.4 to 1.8 mm; the coating material III is 120 g / m 2 The prepreg C is obtained by brushing it onto a quartz cloth. The prepreg C has a layer thickness of 0.4 to 0.8 mm.